Achieving agricultural revitalization: Performance of technical innovation inputs in farmland and water conservation facilities - Ganlin Pu (Alexandria Engineering Journal, 2022)
This article aims to explore the impact of fixed input or the non-discretionary inputs on estimating the input of individual farmland water conservation facilities and its effect on the performance of regional agricultural area in China. The present study developed the production function model and the occasional cost boundary function from the duality of the production, to estimate the technical efficiency of the benefitted farmland area from constructing and improving irrigation and drainage facilities by using Statistics in Taiwan and Zhejiang Province. Considering the presence of fixed inputs or non-discretionary inputs in the investment, construction, and operation of water conservation facilities, the present study estimated the production efficiency of individual farmland water conservation facilities. The empirical results showed that fixed input, or non-discretionary inputs, had a significant impact on the efficiency estimation of farmland water conservation facilities. Technical efficiency would be underestimated if fixed inputs is not considered.